Correlates of justice encounter in service recovery and word-of-mouth publicity - Hart O. Awa; Ojiabo Ukoha; Ogwo E. Ogwo (Cogent Business & Management, 2016)
This paper examines word-of-mouth publicity as an outcome of consumer perception of equitable recovery programs. Survey data were drawn from 317 teachers of Federal Government Colleges and 79 executives of mobile telephone firms in the southeastern and south–south zones; this sample came from locations where Global Systems for Mobile Communications and Code Data Multiple Access networks have interface. Using the partial least square to analyze the data, the path coefficients with their respective t-values greater than 1.96 confirm that the justice dimensions have statistically significant relationship with word-of-mouth. Thus, the manipulation of justice dimensions in the events of service failure affects customers' advocacy behavior. The study recommends proactive and relational approaches in dealing with customer issues as well as fair and equitable recovery and complaint handling programs to suit the needs of the complainants, get them satisfied, and to cause them to progress in the loyalty ladder.
Keywords: 650